2010
DOI: 10.4103/1477-3163.67074
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and lung cancer: Biology and applications in diagnosis and prognosis

Abstract: MicroRNAs are tiny non-coding RNA molecules which play important roles in the epigenetic control of cellular processes by preventing the translation of proteins from messenger RNAs (mRNAs). A single microRNA can target different mRNAs, and an mRNA can be targeted by multiple microRNAs. Such complex interplays underlie many molecular pathways in cells, and specific roles for many microRNAs in physiological as well as pathological phenomena have been identified. Changes in expression of microRNAs have been assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…These findings indicate that dysfunctions of miRNAs may be associated with NSCLC. Recent studies have identified a series of miRNAs that are deregulated in NSCLC, including miR-205 (11). It was shown that ectopic expression of miR-205 in endometrial cancer promoted tumor proliferation and invasion (12).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that dysfunctions of miRNAs may be associated with NSCLC. Recent studies have identified a series of miRNAs that are deregulated in NSCLC, including miR-205 (11). It was shown that ectopic expression of miR-205 in endometrial cancer promoted tumor proliferation and invasion (12).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of miRNAs in NSCLC have been widely studied, and critical regulators of miRNA biogenesis, Dicer, DGCR8, and Drosha, have been reported to be disrupted in lung cancer [8,9]. miRNA microarrays studies have identified many miRNAs aberrantly expressed in lung cancer [10]. Among them, miR-16 was substantially decreased [11].…”
Section: Introductionmentioning
confidence: 99%
“…After the first two miRNAs were found to target Bcl-2, an anti-apoptotic molecule that preserve the survival of malignant B cells so that are important for the pathogenesis and progression of chronic lymphocytic leukemia [7], the potential roles of miRNAs in the cancer etiology have been widely studied and some of miRNAs were identified as oncomirs [8]. In lung cancer, it is reported that the expression profile of a number of miRNAs are disrupted [9,10]. Among them, miR-143 (also named as miR-143-3p) is substantially downregulated.…”
Section: Introductionmentioning
confidence: 99%